Capturing the Potential Implementation of Islamic Financing with Supply Chain Finance Model Fisheries Sector in Belitung - Reviandi Ramadhan; Evony Silvino Violita (Universitas Muhammadiyah Malang, 2024)
This research aims to analyze the Islamic financing model with supply chain financing and its impact for the economic development, especially for fisheries households in Belitung region. This research uses a qualitative approach. The main object of this research was Bank Pembiayaan Rakyat Syariah and the fishery sector in Belitung. In addition, the distribution of the locations of fisheries households consists of 5 (Five) subdistrict namely: Tanjung Pandan, Membalong, Sijuk, Badau, and Selat Nasik. In this study, the research uses a basic framework of interview questions to 10 infromants from multi-channel financing business model study by Bank Indonesia (2023). The results of this study found that the supply chain financing model with Islamic financing contracts has the potential prospect to be applied by using the musharakah and wakalah bil ujrah contract of transactions for fisheries households in five subdistrict of Belitung region. The implication of this research to enhance the critical role of the Islamic financing model for fisheries households to increase the income of fisherman exchange rate in Belitung Regency